Resource rents, democracy and corruption: Evidence from Sub-Saharan Africa - Rabah Arezki; Thorvaldur Gylfason (Center for Economic Studies and ifo Institute (CESifo), 2011)
We examine the effect of the interaction between resource rents and democracy on corruption for a panel of 29 Sub-Saharan countries during the period from 1985 to 2007. We find that higher resource rents lead to more corruption and that the effect is significantly stronger in less democratic countries. Surprisingly, we also find that higher resource rents lead to fewer internal conflicts and that less democratic countries face not a higher but a lower likelihood of conflicts following an increase in resource rents. We argue that these findings can be explained by the ability of the political elites in less democratic countries to more effectively quell the masses through redistribution of rents to the public. We support our argument by documenting that higher resource rents lead to more (less) government spending in less (more) democratic countries. Our findings suggest that the mechanisms through which resource rents affect corruption cannot be separated from political systems.
Keywords: C33; D73; D74; D72; H21; 330; resource rents; corruption; political systems; internal conflicts